How Much Voicing in Voiced Geminates? The Laryngeal Voicing Profile of Polish Double Stops - ROJCZYK, Arkadiusz; PORZUCZEK, Andrzej (Archives of Acoustics, 2024)
Geminates (such as the double /k/ in Polish lekki “light”) form a group of consonants that are mainly characterized by longer durations than the corresponding singletons. Most of the research has concentrated on durational and spectral properties of geminates in contrast to singletons. Much less attention has been paid to the realization of the voicing contrast in geminates and whether it is differently implemented than in singletons. In the current study, we contribute to this research with the data from Polish stop geminates. To this end, a total of 49 native speakers of Polish produced all stop geminates and corresponding singletons in wordforms of the same phonological make-up. The measurements included closure duration, voicing ratio, duration, and mean intensity of the release burst. The results showed that the voicing ratio was 0.69, classifying Polish stop geminates as mildly devoiced. There was a significant speaker-dependent variability in that some speakers devoiced all geminates, while others either partially devoiced or never devoiced. The analysis of interactions between geminates and singletons revealed that geminates cancelled voicing cues observed in singletons such as longer durations and lower intensity of the release burst. We discuss the current results in terms of voicing implementation in Polish and in relation to other geminating languages.